(3bQI cd Yjf aj efGbH SjOfG GdMSjfs - (3GdYdhqj GdTGaYqj GdLaQj, eMeO Hf MSjf, J (B1186 (3g`s ((3jhSa Hf eMeO MeGOs)
(3ChdgG (B:s
(3gPg bUjOI SjOfG GdMSjf QVj Gddg Yfg (B: (3NjQI Gddg ef GdNdb CHj HYO LOj hCfG Hf GdNqjQjf (B** (3Cej GdRgQGA MbG hCHj hEQK GdYde hehdi GdKbdjf (B...s
(3BNQgG (B:s
... (3hjG Ggd HOQ hGdUMGHI cdge hGdJGHYjf dge OheG SQeOG hHYHOc GdfYeGf Ke HeGdc hGdTGaYj bWH GdhLhO hGMeOG (B...(3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\104s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs